Laptop Casing Aesthetic Improvement - Maidin, Shajahan; Wan Malek, Wan Nasuha (Universiti Teknikal Malaysia Melaka, 2014)
This project is designed to take the advantage of additive manufacturing (AM) process in order to improve the aesthetic value of a laptop casing.The aesthetic value includes the overall form of the product,colour and surface of the product.The advantages of AM are able to produce complex shapes without need to consider the process-material-shape attribute.Literature review confirms that AM application in laptop casing particularly to improve the aesthetic aspects has not been done.Typically,laptop cases are poorly designed and do not integrate the cooler fan in the design.To overcome this,a new design of laptop case was proposed with improvement on the geometrical features and the prototype was fabricated directly via a Fused Deposition Modeling machine.A comparative study of the laptop produced by injection molding,handmade and AM was made.Based from a survey from the user,the design produced by AM are more aesthetically pleasing,more attractive and have complex shape compared with injection molded and handmade laptop case.The paper ends with the suggestion of the suitable AM system and the suitable material for the laptop casing.